Induced Marine Fungus Chondrostereum sp. as a Means of Producing New Sesquiterpenoids Chondrosterins I and J by Using Glycerol as the Carbon Source - Hou-Jin Li; Wen-Han Jiang; Wan-Ling Liang; Jia-Xin Huang; Yu-Fei Mo; Yan-Qing Ding; Chi-Keung Lam; Xiao-Jun Qian; Xiao-Feng Zhu; Wen-Jian Lan (Marine Drugs, 2014)
Chondrostereum sp., a marine fungus isolated from a soft coral Sarcophyton tortuosum, can yield hirsutane framework sesquiterpenoids. However, the metabolites profiles vary dramatically with the composition change of the culture media. This fungus was cultured in a liquid medium containing glycerol as the carbon source, and two new metabolites, chondrosterins I and J (1 and 2), were obtained. Their structures were elucidated primarily based on MS, NMR and X-ray single-crystal diffraction data. By comparison with the known hirsutane sesquiterpenoids, chondrosterins I and J have unique structural features, including a methyl was migrated from C-2 to C-6, and the methyl at C-3 was carboxylated. Compound 2 exhibited potent cytotoxic activities against the cancer cell lines CNE-1 and CNE-2 with the IC50 values of 1.32 and 0.56 μM.